A Case Study on Formative Elements and Visual Perception Theory Expressed in Virtual Art Contents - Jung, Chang Yong (International Journal of Membrane Science and Technology, 2023)
With the development of media, the form of expression has rapidly grown into the field of virtual art. The trend of development and generalization of virtual space art through virtual space and virtual reality is forming interest in virtual art using computer graphics, such as information and material, space and time, reality and virtuality, and active participation. The purpose of this paper is to analyze the image contents expressed in virtual art based on the Gestalt theory of form, and to study the aesthetic characteristics of the formative elements and principles of visual perception expressed in virtual art contents. As a result, the aesthetic expression of formative elements and principles of visual perception can feel illusion or virtual expression. In addition, it was confirmed that virtual art was applied with free spatiality that is not limited by space. It was found that the Gestalt theory could play a role in identifying and understanding the meaning expressed in virtual art.